A real‐time touch control system design based on field‐programmable gate array via optimizing Bresenham algorithm for electrowetting displays. Issue 7 (16th March 2021) - Yi, Zichuan; Zeng, Wenjun; Ma, Caiyun; Feng, Haoqiang; Yang, Jianjun; Liu, Liming; Zhang, Zhi; Shui, Lingling; Zhou, Guofu; Zhang, Chongfu
Abstract: Electrowetting displays (EWDs) have the advantages of fast response speed and extremely low energy consumption. However, the function of real‐time touch control has not been realized in EWDs, and the rendering of hand‐drawn lines by a pixelated display has room for improvement, especially in the diagonal directions. The issue of clearly rendering diagonal lines drawn by touch control is not specific to EWDs, and the solution we offer can be beneficial to other display technologies. In this paper, a real‐time touch control system, which was based on field‐programmable gate array (FPGA) by optimizing Bresenham algorithm, was realized in EWDs. In hardware, Nios II processor was used as a main controller, I 2 C bus communication mode was used to establish a communication between a touch screen and the main controller, and MXEI1480 and MXEI2240 were used as driving chips to complete the design of EWD driver module. In software, Bresenham algorithm was optimized to add pixel points at diagonal corners for improving the clarity of line rendering. Then, touch coordinates were transmitted to the EWD driver module for displaying lines rendered. Experimental results showed that the lines rendered on the display by the optimized Bresenham algorithm were thicker and clearer. Abstract : Electrowetting displays (EWDs) have advantages of fast response speed and extremely low energy consumption. A real‐time touch control system, which was based on a field‐programmable gate array (FPGA), was realized for EWDs. Bresenham algorithm was optimized to add pixel points at diagonal corners for clear lines display.